Therapeutic potential of repaglinide-embedded chitosan hydrogel in promoting wound healing - Chou-Yi Hsu; Eman Raeed Azzam; Mohammed Merza; Marwah Suliman Maashi; Ahmed Hjazi; Rekha M.M.; Subhashree Ray; Kapil Ghai; Udaybir Singh; Narges Fereydouni (Regenerative Therapy)
Introduction: This study explores the potential of repaglinide-loaded chitosan-based hydrogels (Hy-R1% and Hy-R3%) as multifunctional scaffolds for wound healing applications. It aims to evaluate their physicochemical properties, cytocompatibility, antibacterial activity, and in vivo healing potential. Methods: The hydrogels were prepared by dissolving chitosan in acetic acid, followed by the incorporation of repaglinide. In vitro assessments, including morphology, swelling, degradation, cytocompatibility, and antibacterial activity, were performed. In vivo wound healing was tested in a rat model using full-thickness wounds. Results: Hy-R3% exhibited superior properties in surface morphology, swelling behavior, and degradation rate compared to the control. It also demonstrated the highest cell viability and significant antibacterial activity against Staphylococcus aureus. In vivo, Hy-R3% accelerated wound closure, showed superior re-epithelialization, and improved collagen deposition. Histological analysis confirmed better tissue remodeling and minimal inflammation in Hy-R3%. Conclusions: Repaglinide-loaded chitosan-based hydrogels, particularly Hy-R3%, represent a promising new therapeutic approach for wound healing. The formulation demonstrated enhanced physicochemical and biological properties, including rapid wound closure and improved tissue regeneration. These findings suggest that repaglinide can be repurposed for wound healing applications, particularly for chronic and diabetic wounds, and lay the foundation for future studies on its broader regenerative potential.